Delayed Timing of Insemination Relative to Estrus Improves Pregnancy to Artificial Insemination With Sex-Sorted Semen in Beef Heifers - K. Aubuchon; J. A. Odde; A. R. Hartman; K. E. Fike; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective was to evaluate the effect of timing of artificial insemination (AI) relative to the onset of estrus on pregnancy outcome when using sex-sorted semen in beef heifers. Study Description:Beef heifers were subjected to the melengestrol acetate with prostaglandin (MGA-PG) estrous synchronization protocol and visually observed for estrus every four hours for five days following injection of PG. Following detection of estrus, heifers were inseminated with semen sorted to contain X-chromosome bearing sperm cells (4.0 × 106live cells per 0.25 mL straw of SexedULTRA 4M). Heifers were retrospectively categorized into one of three intervals from estrus onset to insemination: 1) 12.5–15.9 hours; 2) 16.5–21.0 hours; and 3) 21.4–27.5 hours. Results:Heifers with the shortest interval (12.5–15.9 hours) from estrus onset to insemination had a similar (P>0.10) AI pregnancy rate as compared with heifers with the interval from estrus onset to insemination of 16.5 to 21 hours. Heifers inseminated 21.4 to 27.5 hours following estrus onset achieved a greater (P≤ 0.05) AI pregnancy rate than heifers inseminated 12.5 to 15.9 hours following estrus onset. The Bottom Line:Insemination of beef heifers with sex-sorted semen later than 21 hours after estrus onset appears to improve pregnancy rate to AI when compared to earlier insemination times.
Keywords: sex-sorted semen; beef heifers; artificial insemination